Guidelines for the Complete Transesophageal Echocardiographic Examination - V. V. Lazoryshynets; V. M. Kovalenko; A. V. Rudenko; R. M. Vitovskyy; O. S. Sychov; Y. A. Ivaniv; V. M. Beshliaga; O. A. Krikunov; S. V. Potashev; A. O. Rusnak; L. M. Hrubyak; S. I. Deyak; et al. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Transesophageal echocardiography (TEE) today is a crucial cardiovascular visualization method. Close adherence of esophagus to the majority of cardiac structures and major vessels guarantees excellent ultrasound window compared to trans-thoracic echocardiography (TTE) in certain patients with specific diagnosis, as well as during the majority of cardiac surger-ies and catheter interventions. This paper is developed based on contemporary worldwide experience in TEE and is meant to be used as guidelines for performing TEE in the following situations: 1) diagnostic TEE to solve specific diagnostic tasks; 2) intraprocedural TEE during surgical and catheter interventions. Although these Guidelines contain the recommended protocol of image acquisition, the order and quantity of slices may significantly vary depending on indications for TEE. In some indications concerning specific conditions, additional special slices are recommended, which are described in “Spe-cific Structural Imaging” section of this document. The Guidelines are not intended to review all specific indications for TEE or to cover all anomalies visualized by this modality. This section contains the second out of three parts of the guidelines.